Influence of the main neutron absorbers poisons coupled to the Point Kinetics model by the Rosenbrock’s method - Natália Barros Schaun; Fernanda Tumelero; Claudio Zen Petersen (Brazilian Journal of Radiation Sciences)
In this work, the Neutron Point Kinetics equations are solved for six groups of delayed neutron precursors and different types of ramp reactivity, considering the temperature effects by the Rosenbrock’s method, to verify the methodology. Furthermore, the classical model is solved by inserting the effects of the main neutron poisons, considering constant reactivity for a group of precursors. The simulation consists of inserting a negative constant reactivity, simulating a reactor in its shutdown phase. Then, positive constant reactivity is inserted, simulating power resumption in a reactor already poisoned, to analyzing the final behavior of the neutron density. The simulation achieved its goal of simulating the behavior of the neutron poisons, so that the graphs make physical sense as expected. Therefore, it was found that the proposed method overcame the stiffness of the Neutron Point Kinetics model, and also solved a nonlinear problem by the inclusion of temperature and neutron poisons in the system.